Analisis Rencana Kebijakan Pelibatan Ekspatriat pada Jajaran Direksi di PT. Garuda Indonesia - Raihani Khairunissa Barni; Syarach Agusti Ekasuci; Ayu Maulani; Sabillah Azhari; Tati; Abdullah Qiqi Asmara (Universitas 17 Agustus 1945 Semarang, 2026)
The policy of involving expatriates in the board of directors of State-Owned Enterprises (SOEs) has become a debated issue, particularly regarding its implications for corporate governance and national workforce interests. The main problem discussed in this article is how the policy of expatriate involvement in the board of directors of PT Garuda Indonesia is viewed from the perspective of Good Corporate Governance (GCG). This study aims to analyze the suitability of the policy with GCG principles and its implications for corporate governance and company performance. The research method used is a literature review by examining laws and regulations, academic journals, policy reports, and other relevant secondary sources. The analysis is conducted based on five main GCG principles, namely transparency, accountability, responsibility, independence, and fairness. The results show that the involvement of expatriates in the board of directors of PT Garuda Indonesia has the potential to strengthen corporate governance through the adoption of global managerial standards, improvement of institutional credibility, and acceleration of organizational transformation and efficiency. However, this policy also faces challenges, especially related to transparency in the selection process and the assurance of knowledge transfer to local human resources. It can be concluded that the expatriate involvement policy will provide optimal benefits if it is implemented consistently with GCG principles and accompanied by a strong commitment to strengthening local managerial capacity.